CC Thinker: Mobile-based Assessment to Train Creative and Critical Thinking in Students - Ridhoni, Wahyu; Punaji Setyosari; Dedi Kuswandi; Saida Ulfa; Dahlia Janan (International Journal of Interactive Mobile Technologies (iJIM), 2022)
This research aims to combine assessment of creative and critical thinking in a mobile device context, to see its effect on the creative and critical thinking of students. Design-based research as the method was used to develop the assessment as learning. It is begun with the assessment model and android application development, also experiments in the end. Three assessment sessions are participated by 46 students. The analysis using Kruskal Wallis gains the result that there are significant differences in the creative thinking (Chi-square 18.245, Asymp. Sig 0.000) and the critical thinking (Chi-square 7.620. Asymp. Sig 0.022). A significant difference in creative thinking is seen since the second session, while the difference in critical thinking needs the time up to the third session.